Changes in external costs and infrastructure costs due to modal shift in freight transport in North-western Europe - Olaf Jonkeren; Klaas Friso; Lourentz Hek (Journal of Shipping and Trade (JST), 2023)
Modal shift in freight transport entails moving freight from road to rail, inland waterways, and short sea shipping. In current Dutch and European freight transport policy, modal shift is foreseen to play an important role to mitigate external effects of freight transport. Policy efforts on modal shift are legitimate because the size of the external costs of freight transport are considerable. But can modal shift policies also be effective? In other words, can policy efforts on modal shift result in a decrease of external costs and infrastructure costs due to freight transport? Our research approach falls apart into three steps. In the first step we analyse the transported weight by road on four international freight corridors in North-western Europe that could be transported against at least 10% lower private costs by rail or inland waterways. The share of road transport (transported weight) on the corridors in total road transport in the Netherlands is about 10%. The weight of the cargo that could potentially be shifted on the basis of the transport cost criterium is called the modal shift potential (MSP). We estimate the MSP for the base year 2018 and for the future year 2050. Also in this step, we translate the MSP into changes in transport performance per transport mode. In the second step we determine differences in external costs and user dependent infrastructure costs per unit of transport performance (tonkm) between the transport modes road, rail, and inland waterways. The following external effects are included: greenhouse gas emissions (tank-to-wheel), air pollutant emissions (tank-to-wheel), noise, traffic accidents, congestion, and emissions from fuel and electricity production (well-to-tank) for freight vehicles. Including all these effects, we take a more integral approach than existing studies on the effect of modal shift on the external costs of freight transport. In the third step, we combine the results of steps 1 and 2 and calculate the changes in external costs and infrastructure costs that result from the MSP's. We find MSP's of between 35 and 55%, depending on the market segment (container, or non-container transport, and year). These percentages may seem substantial, but we emphasize that on the freight transport corridors rail and inland waterways are (very) competitive to road. Estimates for the decrease in external- and user dependent infrastructure costs if the MSP's are fully realized point to reductions of exteuro67 million to exteuro150 million for the Netherlands, and exteuro87 million to exteuro136 million abroad for 2018 (considering all countries through which the corridors pass). We emphasize that these are maximum annual savings which can only be achieved if all non-transport cost obstacles for modal shift can be removed. For 2050 estimating a maximum and minimum for the change in external- and infrastructure costs is impossible due to uncertainties in the development of the transport costs and the external costs of freight transport. Because for the year 2018 the MSP's result in a decrease of external costs and infrastructure costs from freight transport on the corridors, we conclude that in the coming years policy efforts on modal shift can be effective. We can however not conclude anything about the efficiency: are the benefits of policy efforts on modal shift larger than the costs? If that is not the case, taking modal shift measures can eventually not be justified from an economic welfare point of view.
Keywords: 650; External costs; Freight transport; Infrastructure costs; Modal shift; Modal shift potential